Outcome of out-of-hospital cardiopulmonary arrest in children: A multicenter cohort study - Kurt, Funda; Bayrakcı, Benan; Tekşam, Özlem; Tekin, Deniz; Derinöz, Okşan; Polat, Emine; Oğuz, Sinan; Gültekingil, Ayşe; Ödek, Çağlar; Tuygun, Nilden; Derbent, Murat; Kalkan, Gökhan; et al. (The Turkish Journal of Pediatrics, 2018)
The aim of this study was to evaluate the demographic characteristics of children who experienced out-of-hospital cardiopulmonary arrest (CPA), and to assess the impact of the bystander cardiopulmonary resuscitation (CPR) on the survival rate of witnessed arrests and the effects of the arrest and CPR durations on the neurological outcomes. This multicenter, retrospective study included a total of 182 patients who underwent CPR for out-of-hospital CPA between January 2008 and December 2012 at six centers in Ankara, Turkey. The median [interquartile range (IQR)] age was 22 (5-54) months; 60.4% of the patients were males, and 44% were younger than one year of age. The witnessed arrest rate was 75.8% (138/182) and the rate of bystander CPR was 13.9% (13/93). In these patients the rate of the return of spontaneous circulation (ROSC) was higher (76.9%). Following resuscitation in the patients for whom the spontaneous circulation was able to be returned, the median (IQR) duration of arrest was 5 (1- 15) min, while it was 15 (5-40) min for the remaining patients (p < 0.001). The ROSC rate was 94.9% in patients who underwent CPR for less than 20 min and 22% in patients requiring CPR longer than 20 min (p < 0.001). Survival to hospital discharge was 14.3%. Of these patients, 57.7% experienced neurological disability. The short duration of an arrest and the presence of CPR are both critical for survival. We suggest that a witness to the CPA, performing early and efficient CPR, yields better results.